1997
DOI: 10.1111/j.1749-6632.1997.tb51878.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunology of the Middle Ear: Role of Local and Systemic Antibodies in Clearance of Viruses and Bacteria

Abstract: Acute otitis media may be defined as the sudden onset of inflammation in the middle-ear space characterized by ear pain and a bulging, thickened, and immobile tympanic membrane. The middle-ear fluid is typically purulent. A bacterial pathogen is recovered in 75% of the episodes. Streptococcus pneumoniae predominates at 35%, followed by nontypeable Hemophilus influenzae at 25%, and Moraxella catarrhalis at 15%. The remaining 25% of middle-ear fluids are sterile and presumably represent viral infections. Increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Interestingly, however, a strong correlation was observed between IgG antibody levels in serum and IgG antibody levels in MEF, for both M. catarrhalis and pneumococcal proteins for the whole study cohort. This is an interesting finding, as it indicates that serum antibody levels are predictive of the presence of local (middle ear) IgG antibody (14,17) and raises the possibility that the measurement of OM pathogen-specific IgG antibodies in the middle ear may be achieved by simply measuring OM pathogen-specific IgG antibody levels in serum. At this moment in time, however, it is not known whether OM pathogen-specific IgG is actually produced locally in the middle ear or transudes into the middle ear from the general circulation (4,14).…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, however, a strong correlation was observed between IgG antibody levels in serum and IgG antibody levels in MEF, for both M. catarrhalis and pneumococcal proteins for the whole study cohort. This is an interesting finding, as it indicates that serum antibody levels are predictive of the presence of local (middle ear) IgG antibody (14,17) and raises the possibility that the measurement of OM pathogen-specific IgG antibodies in the middle ear may be achieved by simply measuring OM pathogen-specific IgG antibody levels in serum. At this moment in time, however, it is not known whether OM pathogen-specific IgG is actually produced locally in the middle ear or transudes into the middle ear from the general circulation (4,14).…”
Section: Discussionmentioning
confidence: 97%
“…When assayed against the four region peptides, the middle ear fluids specifically recognized and bound to the region 3 and 4 peptides, beginning approximately 4 weeks after challenge but already showing lessened reactivity 5 weeks after challenge. Since total antibody available in middle ear fluids represents both locally produced antibody as well as antibodies contributed by serum transuded into the middle ear space during inflammation (2,(16)(17)(18)(19)57), this delayed reactivity of the middle ear fluids to these peptides may have represented the prolonged period of time required for serum antibodies to transude into this highly inflamed space during an active disease of this type. However, these data may also be indicative of the time point at which region 3-and 4-specific antibodies were available for detection in this assay system despite their presence in these fluids at a much earlier point in time and for a more extended period of the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…We had previously demonstrated that infection with IAV induces an influx of neutrophils into the middle ear cavities of infant mice (3). Moreover, pneumococci in the ear colocalize with this influx of neutrophils (3), and neutrophils are thought to interact with antibodies in the middle ear (19). In light of the suggested role of NETs in OM (14, 15), we reasoned that antibodies in the middle ear may facilitate bacterial outgrowth by inducing NETs.…”
Section: B6mtmentioning
confidence: 99%
“…Pneumococcal OM predominately develops in the absence of preexisting immunity, with incidence peaking between 6 months (when maternal antibodies have waned) and 2 years, when specific immunity develops (19). In these immunologically naive individuals, natural antibodies may represent an important defense mechanism against influenza virus-mediated pneumococcal disease, as is seen in pneumococcal sepsis (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation